REVITALISASI KERAJINAN SENI PRASI SEBAGAI KARYA SENI DI DESA SIDEMEN - DARMANA, KETUT; MURNIASIH, ANAK AGUNG AYU; SUCI, NI KETUT (Buletin Udayana Mengabdi, 2012)
ABSTRACT. Prasi art is categorized into genre (school) of two demensional visual art. According to the view of Sidemen villagers, prasi craftsmanship is called ?komik prasi lontar traditional/traditional comic of palm leaf. The process of prasi craftsmanship is shaped out of hand carving using pengerupak (small knife with pointed and sharp tip) on palm leaf (palmyra). Therefore, it look very unique, complicated, and difficult. The softness and thickness of hand carving indeed gives typicality to prasi craftsmanship that is classic and traditional in nature.Training for prasi craftsman to improve their expertise and resources covers two aspects: (1) practical knowledge about techniqueof making the carve on a palm leaf, and (2) knowledge related to the understanding of text of Hindu?s literature as source (babon) which are used as themes in the prasi such as kekawin and parwa (old Javanese metre), kidung (tengahan metre), and tantri. This is so arranged knowing the fact that prasi is a work of art whose essence constitute transformation of literary text to shadow puppet miniature visuals.The training indeed has its response from prasi craftsman. This is evident from all the activities that were attended regularly and the participants were very serious and involved in discussions anticipating the problems that might arise and are relatable to the products of prasi. The applicative training was realized in the form of practical matters and they were put into practice directly and completed duly although in the choice of themes they were given fredom based on their capability. Besides that, the training can give development to prasi art if looked at from the model of its design that is elaborated with classical and modern art, but it is inseparable form its traditional elements. With respect to its quality, prasi art still needs to have the attention and improvemeent in terms of esthetics (art beauty) so as a work of art it always gives satisfaction and enjoyment to the art lovers themselve.